Proteomic Responses to Alkali Stress in Oats and the Alleviatory Effects of Exogenous Spermine Application - Bai, Jianhui; Jin, Ke; Qin, Wei; Wang, Yuqing; Yin, Qiang (Frontiers in Plant Science, 2021)
Alkali stress limits plant growth and yield more strongly than salt stress and can lead to the appearance of yellow leaves; however, the reasons remain unclear. In this study, we found that (1) the down-regulation of coproporphyrinogen III oxidase, protoporphyrinogen oxidase, and Pheophorbide a oxygenase in oats under alkali stress contributes to the appearance of yellow leaves (as assessed by proteome and western blot analyses). (2) Some oat proteins that are involved in the antioxidant system, root growth, and jasmonic acid (JA) and indole-3-acetic acid (IAA) synthesis are up-regulated in response to alkalinity and help increase alkali tolerance. (3) We added exogenous spermine to oat plants to improve their alkali tolerance, which resulted in higher chlorophyll contents and plant dry weights than in plants subjected to alkaline stress alone. This was due to up-regulation of chitinase and proteins related to chloroplast structure, root growth, and the antioxidant system. Spermine addition increased sucrose utilization efficiency, and promoted carbohydrate export from leaves to roots to increase energy storage in roots. Spermine addition also increased the IAA and JA contents required for root growth.